以下关于Z变换正确的是:()。
A: [img=104x25]18031d9c69da425.png[/img]的Z变换是[img=219x46]18031d9c74517f8.png[/img]
B: [img=121x27]18031d9c7cf2a2e.png[/img]的Z变换是[img=209x50]18031d9c878b5cd.png[/img]
C: [img=56x27]18031d9c90754d8.png[/img]的Z变换是[img=122x40]18031d9c98c7b9b.png[/img]
D: [img=66x26]18031d9ca0e7666.png[/img]的Z变换是[img=166x51]18031d9cac0f42b.png[/img]
A: [img=104x25]18031d9c69da425.png[/img]的Z变换是[img=219x46]18031d9c74517f8.png[/img]
B: [img=121x27]18031d9c7cf2a2e.png[/img]的Z变换是[img=209x50]18031d9c878b5cd.png[/img]
C: [img=56x27]18031d9c90754d8.png[/img]的Z变换是[img=122x40]18031d9c98c7b9b.png[/img]
D: [img=66x26]18031d9ca0e7666.png[/img]的Z变换是[img=166x51]18031d9cac0f42b.png[/img]
举一反三
- 以下关于Z变换正确的是:()。 A: [img=104x25]18035f7b528ee87.png[/img]的Z变换是[img=219x46]18035f7b5c3abde.png[/img] B: [img=121x27]18035f7b654a5a7.png[/img]的Z变换是[img=209x50]18035f7b70f40f3.png[/img] C: [img=56x27]18035f7b7a3dcfb.png[/img]的Z变换是[img=122x40]18035f7b82ea241.png[/img] D: [img=66x26]18035f7b8ba17ac.png[/img]的Z变换是[img=166x51]18035f7b977f8ee.png[/img]
- 以下关于Z变换正确的是:()。 A: [img=104x25]1802fc9fc87095e.png[/img]的Z变换是[img=219x46]1802fc9fd3e62da.png[/img] B: [img=121x27]1802fc9fdc87c18.png[/img]的Z变换是[img=209x50]1802fc9fe8076a9.png[/img] C: [img=56x27]1802fc9ff034ec9.png[/img]的Z变换是[img=122x40]1802fc9ff882b9c.png[/img] D: [img=66x26]1802fca001c9b3c.png[/img]的Z变换是[img=166x51]1802fca00d4c11d.png[/img]
- 已知序列[img=256x24]1803678e98b4830.png[/img],则该序列的Z变换及收敛域为_________。() A: X(z)=[img=32x21]1803678ea0e893d.png[/img] 0<|Z|<1 B: X(z)=[img=28x21]1803678eaa26630.png[/img] 0<|Z|<[img=18x14]1803678eb1c8a78.png[/img] C: X(z)=[img=32x21]1803678ea0e893d.png[/img] 0<|Z|<[img=18x14]1803678ec1ba1fe.png[/img] D: X(z)=[img=32x21]1803678ea0e893d.png[/img] 0<|Z|[img=14x21]1803678ed3103a6.png[/img][img=18x14]1803678ec1ba1fe.png[/img]
- 已知 X(z) =[img=104x45]180306b0320c88a.png[/img], 1<|z|< 2,则X(z)的反变换( )。 A: [img=233x25]180306b03cf86b5.png[/img] B: [img=229x25]180306b046b9121.png[/img] C: [img=205x25]180306b05176cdf.png[/img] D: [img=220x25]180306b05b55007.png[/img]
- 已知 X(z) =[img=104x45]180306ada7dcc7b.png[/img], 1<|z|< 2,则X(z)的反变换( )。 A: [img=233x25]180306adb3c56cc.png[/img] B: [img=229x25]180306adbf797f9.png[/img] C: [img=205x25]180306adcbb3da4.png[/img] D: [img=220x25]180306add69adda.png[/img]